A brief analysis of Paulo Freire's pedagogy of the oppressed and Aníbal Ponce's education and class struggle (Revista Contexto & Educação, 2025)
Paulo Freire's "Pedagogy of the Oppressed" deals with the false generosity of the oppressor in its examination of the formation of a critical and reflective conscience among peasants who have been dehumanized by the capitalist system. The work of philosopher Aníbal Ponce is added to Freire's thinking on contributions to the field of education. This article analyzes and discusses the book "Educação e Luta de Classes", with a view to reflecting on the educational process in history, with regard to the categories: work, alienation, education and class division. To this end, the school education process was related, with an emphasis on resistance to neoliberalism in schools, with the reflective analyses of educators Paulo Freire, Aníbal Ponce, Demerval Saviani and Georg Lukács. The bibliographical research - carried out during the period of a Master's research in Education linked to the Postgraduate Program in Education at the Federal University of Amapá (UNIFAP) - is based on criticism of the process of class struggles. The conclusion was that the process of denial and alienation of learning rights by the oppressor and dominant classes towards the working class historically triggers a process of oppression of the working class to prevent its social ascension through literacy and study.
Keywords: Pedagogy of the Oppressed; class struggle; class consciousness